2012
DOI: 10.1016/j.jclinane.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocephalus with BiPAP use after transsphenoidal surgery

Abstract: While the benefits of continuous positive airway pressure (CPAP) or bilevel positive airway pressure (BiPAP) for patients with obstructive sleep apnea are well described, reports in the literature of complications from its use are rare. A patient who received postoperative BiPAP after undergoing transsphenoidal craniopharyngioma resection developed severe pneumocephalus and unplanned intensive care unit admission. Although the pneumocephalus resolved with conservative management over two weeks, we propose caut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
0
34
0
2
Order By: Relevance
“…In our survey, the majority release patients from activity restrictions between 2 and 6 weeks postoperatively, with increasing lengths of time for intradural repairs. The timing for resumption of positive airway pressure (PAP) devices for obstructive sleep apnea has been empirically suggested by one author to be 6 weeks based on an animal model . PAP use in skull base defects has been reported multiple times as a cause of life‐threatening tension pneumocephalus .…”
Section: Discussionmentioning
confidence: 99%
“…In our survey, the majority release patients from activity restrictions between 2 and 6 weeks postoperatively, with increasing lengths of time for intradural repairs. The timing for resumption of positive airway pressure (PAP) devices for obstructive sleep apnea has been empirically suggested by one author to be 6 weeks based on an animal model . PAP use in skull base defects has been reported multiple times as a cause of life‐threatening tension pneumocephalus .…”
Section: Discussionmentioning
confidence: 99%
“…Certain institutions have demonstrated safely using CPAP, delayed until the third postoperative day after TSS . Animal models have shown that fascial dural repair develops a fibrous ingrowth as early as 2 weeks, and thus some institutions have recommended waiting 6 weeks after dural repair for CPAP use . Other institutions have used CPAP both immediately and 2 to 4 weeks after TSS in OSA patients and reported no correlation with pneumocephalus .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in guinea pigs demonstrated that elevating MEP with air up to 250 daPa had no effect on auditory thresholds measured by auditory brainstem response (ABR) [8]. While it appears that hearing is likely not significantly affected in most individuals, there have been rare reports of tympanic membrane rupture, pneumocephalus, and tension pneumocranium with CPAP use [9][10][11][12]. Although rare, these findings should prompt caution with CPAP use following head trauma, rhinologic or otologic surgery, and particularly following intradural skull base procedures.…”
Section: Discussionmentioning
confidence: 99%